2023
DOI: 10.3390/ph16111631
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin as a Therapeutic Product: Evaluation of Its Pharmacological Action and Clinical Applications—A Review

Mohd Aamir Mirza,
Syed Mahmood,
Ayah Rebhi Hilles
et al.

Abstract: Quercetin is the major polyphenolic flavonoid that belongs to the class called flavanols. It is found in many foods, such as green tea, cranberry, apple, onions, asparagus, radish leaves, buckwheat, blueberry, broccoli, and coriander. It occurs in many different forms, but the most abundant quercetin derivatives are glycosides and ethers, namely, Quercetin 3-O-glycoside, Quercetin 3-sulfate, Quercetin 3-glucuronide, and Quercetin 3′-metylether. Quercetin has antioxidant, anti-inflammatory, cardioprotective, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…The antioxidant, anti-inflammatory, antibacterial, and antiviral effects of the substance have been described. It also has its part to play in the treatment of cardiovascular diseases, cancer, metabolic disorders, and neurodegenerative diseases [189]. The exact molecular mechanisms of quercetin useful for GC therapy are being sought and require further research.…”
Section: Coriandermentioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidant, anti-inflammatory, antibacterial, and antiviral effects of the substance have been described. It also has its part to play in the treatment of cardiovascular diseases, cancer, metabolic disorders, and neurodegenerative diseases [189]. The exact molecular mechanisms of quercetin useful for GC therapy are being sought and require further research.…”
Section: Coriandermentioning
confidence: 99%
“…Research is being conducted into the use of quercitin glucosides, which are more bioavailable than the basic form. It is indicated that nano-quercitin has higher efficacy [189,191]. Another potential way to increase the bioavailability of quercetin is through cryopreservation and microencapsulation [193].…”
Section: Coriandermentioning
confidence: 99%
“…Histopathology was performed to see damage to the heart organ. Quercetin was used as a comparison because of its antioxidant and cardioprotective properties, which are helpful against cardiovascular disease [ 30 ]. The phytochemical constituent analysis of the extract was also carried out using LC-HRMS, and chemical element analysis was performed using GC-MS.…”
Section: Introductionmentioning
confidence: 99%